1988
DOI: 10.1055/s-2007-1018137
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Simultaneous Multiple Gastric Cancers by the Endoscopic Congo Red - Methylene Blue Test

Abstract: The clinicopathological features of simultaneous multiple gastric cancers, and the accuracy of their diagnosis by routine endoscopic examination were analyzed. In addition, the accuracies of diagnosis of coexisting early gastric cancers by routine endoscopic examination and by the endoscopic Congo red--methylene blue test developed in our hospital were compared. The results showed that multiple cancers occurred frequently in elderly male patients, in patients with early gastric cancer of the flat and elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
2
13
1
1
Order By: Relevance
“…The most reliable study was that reported by Kosaka et al [2] , in which all the stomach specimens, 68 patients with gastric cancer were subjected to a serial histological examinations after operations, and accessory lesions were revealed in five (7.4%) cases. In the present study, we observed that SMGC were present in 5.1% of all patients with gastric cancer, that is lower than those reported in previous investigations [10][11][12][13][14] .…”
Section: Discussioncontrasting
confidence: 76%
“…The most reliable study was that reported by Kosaka et al [2] , in which all the stomach specimens, 68 patients with gastric cancer were subjected to a serial histological examinations after operations, and accessory lesions were revealed in five (7.4%) cases. In the present study, we observed that SMGC were present in 5.1% of all patients with gastric cancer, that is lower than those reported in previous investigations [10][11][12][13][14] .…”
Section: Discussioncontrasting
confidence: 76%
“…The surgeon can identify the F-line during operation by the Congo red test, or can estimate more easily only by the appearance of the mucosal folds. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The classification system had the specificity and NPV of 81% and 99%, respectively, to diagnose dysplasia. Congo red alone, or combined with methylene blue, has also been applied in chromoendoscopy [132, 133]. The correct diagnosis of synchronous multiple loci of EGC by Congo red-methylene blue chromoendoscopy could be higher than that of conventional WLI endoscopy (28.3% versus 88.9%) [133].…”
Section: The Application Of Iee In Stomachmentioning
confidence: 99%